Synthesis and Research of Alumina Ceramics Properties - Evgeniy I. Frolov; Polina V. Notina; Sergey V. Zvonarev; Evgeniya A. Il'ina; Vyacheslav Yu. Churkin (Chimica Techno Acta, 2020)
The article describes in detail alumina powder synthesis by different methods at varying parameters. The technique of obtaining ceramics and the research of the optical properties for determining the materials with the maximum luminescence efficiency is presented. The concentration of the luminescence intrinsic centers and various defects differ for ceramics synthesized by different methods. It is determined that ceramics based on the powder synthesized by a sol-gel method has the maximum thermoluminescence intensity in the F-center peak, whereas for the peak of 360 °C it is obtained with the powder prepared by precipitation of aluminum nitrate with a PEG‑20000 stabilizer.